2020
DOI: 10.2174/1574887115666200709142119
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid Level as a Predictive Biomarker of Gestational Hypertension Severity; A Prospective Observational Case-Control Study

Abstract: Background: Pre-eclampsia poses a significant potential risk of hypertensive disorders during pregnancy, a leading cause of maternal deaths. Hyperuricemia is associated with adverse effects on endothelial function, normal cellular metabolism, and platelet aggregation and adhesion. This study was designed to compare serum urate levels in normotensive pregnant women to those with pregnancy-induced hypertension, and to evaluate its value as a potential predictive marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Likewise, this close relationship between UA and hypertension also exists in pregnant women. The level of sUA in pregnant women is higher than that in normal, nonpregnant women, and the incidence of hypertensive disorders of pregnancy is significantly increased in pregnant women with hyperuricemia (Sakr et al, 2020). The mechanisms of increased UA level during pregnancy may be related to the decrease of estrogen concentration, the increase of high purine food intake, and the increase of XO activity.…”
Section: Ua and Hypertensionmentioning
confidence: 99%
“…Likewise, this close relationship between UA and hypertension also exists in pregnant women. The level of sUA in pregnant women is higher than that in normal, nonpregnant women, and the incidence of hypertensive disorders of pregnancy is significantly increased in pregnant women with hyperuricemia (Sakr et al, 2020). The mechanisms of increased UA level during pregnancy may be related to the decrease of estrogen concentration, the increase of high purine food intake, and the increase of XO activity.…”
Section: Ua and Hypertensionmentioning
confidence: 99%
“…Federica et al first reported the relationship between serum UA and hypertension in 1870 . Previous studies have shown that impaired excretion of renal uric acid and the final product of purine metabolism trigger hyperuricemia, whereas elevated levels enhance the development of hypertension in the general population. , Nevertheless, Feig et al discovered that reducing uric acid levels using allopurinol, an inhibitor of xanthine oxidase, lowered blood pressure . Antihypertensive drugs have been shown to affect uric acid levels, and, in turn, most hypouricemia drugs have been shown to have an effect on blood pressure. , Animal and cell experiments revealed that the up-regulation of the RAAS contributed to the role of uric acid in promoting hypertension and inflammatory status .…”
Section: Discussionmentioning
confidence: 99%
“…62 Previous studies have shown that impaired excretion of renal uric acid and the final product of purine metabolism trigger hyperuricemia, 63 whereas elevated levels enhance the development of hypertension in the general population. 62,64 Nevertheless, Feig et al discovered that reducing uric acid levels using allopurinol, an inhibitor of xanthine oxidase, lowered blood pressure. 65 Antihypertensive drugs have been shown to affect uric acid levels, and, in turn, most hypouricemia drugs have been shown to have an effect on blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Üstün and colleagues reported higher levels of hsCRP in patients with mild to severe pre-eclampsia compared to normal pressure controls. They used a nephelometric test to measure CRP levels and found a positive correlation between CRP and mean arterial pressure 19 .…”
Section: Discussionmentioning
confidence: 99%